THE IMPLEMENTATION OF ACTIVE LEARNING-BASED SCIENCE BLOCK TO IMPROVE STUDENTS' ACADEMIC ACHIEVEMENT AND SCIENCE-PROCESS SKILL IN LEARNING MOTION AND FORCE - Adinda Nur Wulandari, - (2019)
Indonesian students are categorized as low performer in science based on PISA and TIMSS survey. Eventhough the current curriculum demand a learning environment that is students-centered, for 6 six years there is no improvemnet in students' science performance due to so many factor, for example the teaching strategies that the teacher uses in class. This study is made to investigate the effect of active learning-based science block towards students' academic achievement and science process skill in learning motion and force. This study uses weak experiment method with the sample of 53 students in one of Junior High School in Bandung City. The result of this research indicates medium improvement of students' academic achievement with the N-gain of 0.35. The highest N-gain is on the subtopic of linear motion with the N-gain of 0.85 and the cognitive level of applying (C3) with the N-gain of 0.78. The science process skill of students was found to be inadequate for all aspects that includes observing skill, inferring skill, and communicating skill whilst their measuring skill was found to be needing an improvement. A further research is desired to measure the changes in students' science process skill through the implementation of active learning-based science block. Keywords: Active Learning, Academic Achievement, Science Process Skill, Motion and Force